PENGARUH DIGITALISASI LAYANAN DAN NPL TERHADAP KINERJA KEUANGAN PT BANK MANDIRI (PERSERO) TBK - Novanti, Hani (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Digital transformation has become the main driver of change in the global banking industry, including in Indonesia. This study aims to analyze the effect of the number of digital transactions and the ratio of non-performing loans (NPL) on the profitability of PT Bank Mandiri (Persero) Tbk, as measured by Return on Assets (ROA) during the period 2015–2024. The method used is a quantitative approach with a multiple linear regression model, preceded by classical assumption tests including normality, multicollinearity, autocorrelation, and heteroskedasticity. The results of the study indicate that the number of digital transactions does not significantly affect ROA, while NPL has a negative and significant effect on ROA. These findings suggest that the success of banking service digitalization does not automatically improve financial performance if it is not accompanied by effective credit risk management. The implication of this study is the importance of integrating digital strategy and risk management in national banking business planning.